Study of histopathological changes of cat’s eyes as a model of malignant neoplasms development - D. A. Vilmis; M. V. Stepanova; L. F. Sotnikova (Российский офтальмологический журнал, 2025)
Paraneoplastic syndromes are clinical and laboratory manifestations of the tumor process. Purpose: to study structural changes in domestic animals (cats) as a model for the development of malignant neoplasms of various origins and localizations based on histopathological analysis of the eyeballs. Material and methods. Histopathological analysis of the eyeballs of 19 cats was performed after bilateral and unilateral enucleation. The experimental group of animals included 12 cats with concomitant oncological diseases: mostly of unspecified morphology (50.0% of cases), in the control group (7 cats) there was no history of oncological diseases. Results. Histological changes in the eyeballs were detected in 36.8% of cats. Histologically significant findings were detected only in the iris of the cats in the experimental group and in the cornea of the control group. The most sensitive of the eyeball structures in the study was the iris. In 16.7% of cats in the experimental group, ophthalmologic syndrome in the form of iris cysts, which developed against the background of oncological diseases, was histologically confirmed. In the etiology of extraocular neoplasms, lymphomas and melanomas were detected to a greater extent — 16.7% each, sarcomas and squamous cell carcinoma — 8.3% of cases. The greatest cancer damage was noted in the sensory organs — 25.0%; mammary gland, lymph nodes, intestines and chest cavity — 16.7% of cases; liver, oral cavity, bladder — 8.3% of cases in the sample. In 21.18% of cases, lesions of two or more organs were established. In 21.1%, histopathological studies made or clarified an oncological diagnosis: melanoma, lymphoma. Conclusion. The study of cytoarchitecture and morphofunctional parameters of the visual organ in the aspect of malignant neoplasm development allows not only to confirm the presence of a tumor, but also to clarify its variant and individual characteristics, which determines the treatment regimen.